Implementasi Cooperative Learning Tipe Think-Pair-Share Dalam Pembelajaran Bercerita Di SMPK Yos Sudarsoh Kecamatan Ende Tengah - Dorothea Germana Mbio (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
This study aimed to describe the application of Cooperative Learning, particularly Think-Pair Share in teaching story-telling skill as one of the productive language skill. This study is a qualitative study. Place of this research at lower scondary school Yos Sudarsoh Kecamatan Ende Tengah. The sources of data include (1) the informant, the teachers and students, (2) events, such as the learning process of story-telling skill using Think-Pair Share, and (3) document. The data collection techniques used in this research include interview, observation, and document analysis. Data analysis techniques used is an interactive technique which is presented in a descriptive form. The results indicate that (1) the stages of learning of the Think-Pair Share as described in the lessosn plan were in accordance with the general stages described in the the theory, (2) the implementation of Cooperative Learning especiallay Think-Pair-Share technique in the teaching learning process was in accordance with what has been described the lesson plan, (3) the appreciation of the implementation of the Cooperative learning method especially the Think-Pair-Share technique was pretty good.